Genipin modified lyophilized platelet-rich fibrin scaffold for sustained release of growth factors to promote bone regeneration - Liu, Xiaoyao; Yin, Mingjing; Li, Ying; Wang, Jianqun; Da, Junlong; Liu, Zhongshuang; Zhang, Kai; Liu, Lixue; Zhang, Wenxuan; Wang, Peijun; Jin, Han; Zhang, Bin (Frontiers in Physiology, 2022)
Lyophilized platelet-rich fibrin (L-PRF) was shown to further activate resident platelets in platelet-rich fibrin causing a higher amount of growth factors release. However, it still required further experimental studies to resolve the uncontrolled degradation and burst release problem. In this study, the nature crosslinker genipin is introduced to improve the performance of L-PRF scaffold. We used a series of gradient concentration genipin solutions to react with L-PRF. The crosslinking degree, micro morphology, mean pore size, water absorption and mechanical properties of the crosslinked scaffold were evaluated. In order to study the effect of genipin modification on the release kinetics of growth factors from L-PRF, we detected the release of platelet-derived growth factor, vascular endothelial growth factor and transforming growth factor in vitro by ELISA. To investigate the biodegradability of the crosslinked L-PRF in vivo, the scaffolds were transplanted subcutaneously into backs of rats, and the materials were recovered at 1, 2 and 4 weeks after implantation. The biodegradation, inflammatory reaction and biocompatibility of the scaffolds were examined by histological staining. Finally, the genipin crosslinked/uncrosslinked L- PRF scaffolds were implanted with freshly prepared SHED cell sheets into rat critical size calvarial defects and the skull samples were recovered to examine the treatment efficacy of genipin crosslinked L-PRF by histologic and radiographic approaches. Results of this study indicated that genipin can be used to modify L-PRF at room temperature at a very low concentration. Genipin-modified L-PRF shows better biomechanical performance, slower biodegradation, good bioavailable and sustained release of growth factors. The 0.01% w/v and 0.1% w/v genipin crosslinked L-PRF have good porous structure and significantly promote cell proliferation and enhance the expression of key genes in osteogenesis in vitro, and work best in promoting bone regeneration in vivo.